Implementation of Good Governance by Village Governments in Efforts to Improve The Quality of Public Services (International Journal of Applied Research and Innovation, 2026)
Population administration services constitute one of the most fundamental public services and serve as an important indicator of the quality of village governance. The implementation of good governance principles is essential for strengthening public service delivery and supporting the realization of the Integrity Zone (ZI) toward a Corruption-Free Zone (WBK) and a Clean and Service-Oriented Bureaucracy Zone (WBBM). This study aims to analyze the implementation of good governance in population administration services at the Weragati Village Government, identify existing institutional challenges, and examine the alignment between current service practices and the Integrity Zone framework. A qualitative descriptive approach was employed using in-depth interviews, field observations, and document analysis. Data were analyzed through data condensation, data display, and conclusion drawing. The findings reveal that population administration services have generally reflected the principles of accountability, transparency, professionalism, and nondiscrimination. However, governance implementation remains insufficiently institutionalized due to the absence of standardized service procedures, uncertain service completion times, limited digital information management, and ineffective complaint mechanisms. These shortcomings indicate that current service practices have not fully satisfied the institutional requirements of the Integrity Zone framework. The study concludes that strengthening standardized governance systems and institutional management is essential for improving sustainable public service quality at the village level.